Komunikasi Terapeutik Rohaniawan pada Pelayanan Spiritual Pasien Gangguan Jiwa - Machrom, Moh. Anung Nailil; Destrity, Nia Ashton (Universitas Brawijaya, 2023)
Therapeutic communication on spiritual services that is often carried out by clergy is one of the activities to help the healing process of mental patients. This study aims to find out and analyze therapeutic communication in spiritual services between clergy and psychiatric patients. This research uses phenomenology method with in-depth interview data collection techniques conducted on four clergy. The results of this study indicate that the clergy interpret mental patients from a biomedical and personalistic perspective. Mental disorders cause erratic physiological actions that make the clergy also interpret spiritual service as an effort to help patients get peace of mind by using religious practices. The stages of therapeutic communication carried out by clergy on spiritual service are the orientation stage, the work stage and the termination stage. Opened with orientation stages, clergy make small talk first to get to know more about psychiatric patients. Continued the work phase which raises religious values, and closes with the termination stage consist of follow up plan and subjective evaluation. Clergy often encounter obstacles to spiritual service, the obstacles are miss communication, emotional instability and the patient's habit of saying abruptly. Spiritual efforts to reduce barriers are guarding emotions, pausing. The method used by clergy in spiritual service is muhasabah, returning to nature, reflection, and release of sin.